Pengaruh Operating Leverage Dan Likuiditas Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Sektor Consumer Goods Industry Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016 - 2018 - Zahrah Nabilah; Sri Hermuningsih; Gendro Wiyono (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
The purpose of this study is to examine the direct and indirect effects of Operating Leverage and Liquidity on Firm Value with Capital Structure as an intervening variable. The sampling technique uses purposive sampling method to determine the sample based on the consideration of researchers. Data analysis uses Partial Least Square (PLS), which is variance-based SEM, with SmartPLS software. The analysis shows that (1) there is a negative and insignificant influence between Operating Leverage on Capital Structure (2) there is a positive and significant effect between Liquidity on Capital Structure (3) there is a negative and insignificant influence between Operating Leverage on Firm Value (4 ) there is a negative and insignificant effect between Liquidity on Firm Value (5) there is a negative and insignificant influence between Capital Structure on Company Value (6) Capital Structure cannot mediate between Operating Leverage and Liquidity on Firm Value.